Pengembangan Modul Pembelajaran Berbentuk Pop-Up dan Smash Book Materi Sifat Cahaya Bagi Siswa Penyandang Disabilitas Rungu - Handayani, Try Lisa; Sugianto, Sugianto; Susanto, Hadi (UPEJ Unnes Physics Education Journal, 2019)
The aim of this research is to develop an IPA (Physics) learning module in form of pop-up and smash book on Nature of Light that tested it is feasibility, effectiveness, and practicality. This research uses Research and Development methode (R & D). Test design using pre-eksperimental design with one group pretest-posttest. Initial test was conducted at SLB Wantu Wirawan and final test was conducted at SLB Negeri Salatiga. The result show that the module in form of pop-up and smash book on Nature of Light was classified feasible by media validator and material validator with media feasibility percentage 90,50% and material feasibility 85,50%. The effectiveness percentage of module 92,00% with N-Gain 0,64 and practicality percentage 92,50%. Based on the result of this research concluded that module in form of pop-up and smash book was proven feasible, effective, and practical to use by deaf students in IPA (Physics) learning, particularly on Nature of Light